Truancy and Implications in Guidance and Counseling - Sari, Utari Mayang; Yusuf, A. Muri; Bentri, Alwen (Universitas Negeri Padang, 2016)
TruancyÂ is an act of stay away from school without permission. . This study was conducted in SMPN 1 Nan Sabaris to ward studentsâ€™ truant behavior. The purpose of this study describes the concept of the school, and the behavior which were shown, the causal factor truant behavior and the effort of guidance and counseling teacher in helping students who have truant behavior. This research was conducted under qualitative in term of case studies research. The purposive and snowball sampling techniques were used to take the sample. Thus the data were obtained from student, parents, friends of the sample student and subject teachers and guidance and counseling teacher. Interview, observation and document analysis were used to collect the data were analyzed through data reduction, presentation and conclusion or verification.